Amylose-wrapped luminescent conjugated polymers. - Frampton, M; Claridge, T; Latini, G; Brovelli, S; Cacialli, F; Anderson, H (2008)
Highly luminescent inclusion complexes consisting of poly(para-phenylene) (PPP) or poly(4,4'-diphenylene-vinylene) (PDV) in the helical cavity of amylose have been synthesised, structurally characterised by nuclear Overhauser spectroscopy and used to fabricate electroluminescent light-emitting diodes.